Performance of mortar and concrete incorporating granite sludge as cement replacement. (30th April 2018) - Mashaly, Ahmed O.; Shalaby, Basel N.; Rashwan, Mohammed A.
Highlights: Feasibility of using granite sludge as a supplementary cementitious material. Three types of mixes were prepared using up to 40% granite sludge replacing cement. A mix of 20% granite sludge meets the requirements of concrete units & cement tiles. Abstract: The main objective of the present study is to determine the feasibility of using granite sludge, produced during the manufacturing processes of ornamental stones, as a cement replacement in mortar and production of concrete blocks by assessing their physical, mechanical and durability performance. The granite sludge as well as cement were characterized using XRF, XRD, particle size distribution, specific surface area and specific gravity. Three types of mixes including "cement paste composites", "mortar" and "concrete" mixes, were prepared where the granite sludge was substituted for cement binder up to 40% at certain proportions of 0%, 10%, 20%, 30% and 40%. The physico-mechanical properties of all three types were determined at 7 d and 28 d, while the durability performance of hardened mortar and concrete mixes was determined at 28 d and 90 d, according to standard test methods of ASTM & BS EN and the results were compared with the specification requirements of these standards as well as Egyptian Standard Specifications (ESS). The test results clearly showed that the mortar and concrete mixes modified with granite sludge up to 20% cement replacement exhibited a negligible decline in physical and mechanical properties in addition to enhanced resistance to abrasion, freeze & thaw and sulfate attack. Furthermore, they are in compliance with the requirements of concrete bricks and paving units as well as mortar cement and cement tiles.